(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
In the context of globalization and rapid technological advancement, the importance of teaching English in modern education has significantly increased. English has become a key tool for international communication, academic mobility, and professional development. This study aims to explore the role of modern educational technologies in enhancing the effectiveness of English language teaching. The research focuses on the integration of digital tools such as online learning platforms, mobile applications, and interactive multimedia in the language learning process. A qualitative approach is employed to analyze theoretical perspectives and practical applications presented by leading scholars in the field of language teaching methodology. The findings reveal that modern technologies c